PENERAPAN MODEL PEMBELAJARAN SCIENTIFIC INQUIRY UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS PESERTA DIDIK PADA SUB MATERI POKOK FLUIDA DINAMIS - Enden Suhila; Chaerul Rochman; Endah Kurnia Yuningsih (Journal of Teaching and Learning Physics, 2016)
The purpose of study is to determine the feasibility of learning processes and increase science literacy skills of learners using ‘Scientific Inquiry’ model of learning on the fluid dynamic. Data katerlaksanaan activity of teacher and students is obtained through observation sheets, while data on the literacy skills of learners is obtained through the test description.The method used in this research is pre-experiment. The study was conducted in Muhammadiyah Al-Furqon senior high school Tasikmalaya class XI IPA-B. The sample in the study were 28 students who were selected using random sampling techniques. The results obtained in this study: (1) feasibility study by using 'Scientific Inquiry' model of learning is in very good category; (2) the literacy skills of learners sins increase in gain results. The magnitude of the increase scientific literacy of students can be seen from the average N-Gain learners of 0.67 categorized being. Thus there is increasing scientific literacy capability of learners through the 'Scientific Inquiry' model of learning in fluid dynamic.